Accelerating Progress towards Achieving Productive Youth Employment and Decent Work - Corbett, Hannah; Kilimani, Nicholas (Institute of Development Studies, 2017)
Realising full, productive employment and decent work for all features prominently among the Sustainable Development Goals (SDGs). In many developing countries, especially in Africa and South Asia, youth constitute nearly a third of the population. Current projections suggest that a billion more young people will enter the job market over the next decade. Hence, issues of youth employment have risen up the political agenda at both international and national levels. Avenues for youth employment creation on a substantial scale must be sought as a matter of urgency. This will involve a re-evaluation of the different issues around labour demand and supply, in addition to rethinking how young people’s entrepreneurial spirit can be harnessed.